A robust, simple, high‐throughput technique for time‐resolved plant volatile analysis in field experiments. (21st May 2014) - Kallenbach, Mario; Oh, Youngjoo; Eilers, Elisabeth J.; Veit, Daniel; Baldwin, Ian T.; Schuman, Meredith C.
Summary Plant volatiles (PVs) mediate interactions between plants and arthropods, microbes and other plants, and are involved in responses to abiotic stress. PV emissions are therefore influenced by many environmental factors, including herbivore damage, microbial invasion, and cues from neighboring plants, and also light regime, temperature, humidity and nutrient availability. Thus, an understanding of the physiological and ecological functions of PVs must be based on measurements reflecting PV emissions under natural conditions. However, PVs are usually sampled in the artificial environments of laboratories or climate chambers. Sampling of PVs in natural environments is difficult, being limited by the need to transport, maintain and provide power to instruments, or use expensive sorbent devices in replicate. Ideally, PVs should be measured in natural settings with high replication, spatio‐temporal resolution and sensitivity, and modest costs. Polydimethylsiloxane (PDMS), a sorbent commonly used for PV sampling, is available as silicone tubing for as little as 0.60 € m−1 (versus 100–550 € each for standard PDMS sorbent devices). Small pieces of silicone tubing (STs) of various lengths from millimeters to centimeters may be added to any experimental setting and used for headspace sampling, with little manipulation of the organism or headspace. STs have sufficiently fast absorption kinetics and large capacity to sample plant headspaces over a timescale of minutes to hours, and thus can produce biologically meaningful 'snapshots' of PV blends. When combined with thermal desorption coupled to GC–MS (a 40‐year‐old widely available technology), use of STs yields reproducible, sensitive, spatio‐temporally resolved quantitative data from headspace samples taken in natural environments.